Information Provision and Active Citizenship: An NGO's Information-Based Interactions. Issue 2 (3rd April 2018) - Connor, Megan; Yerbury, Hilary
Abstract: This study explores the relationships that are created between an Non-Government Organisation (NGO) and its communities by analysing the flows of information which occur on a website and Facebook page, understood as sites for democratic engagement. It brings together Kahn's practical taxonomy of information provision in community-based organisation and Chatman's small world theory with the literature of active citizenship. Two clear perspectives emerged in the NGO's information provision, the first being the focus on provision of information to its primary client group and the second being a focus on a broader audience, including those supportive of its work, through the functions of advocacy and community engagement. The analysis using small world theory identified insiders and outsiders among the Facebook page commenters and showed the variety of ways in which they enacted active citizenship. Importantly, it also demonstrated how choices the NGO made over its use of the Facebook technology affected its engagement with active citizenship. The study concludes that the use of an interdisciplinary perspective, bringing together information studies and understandings of citizenship, has brought insights for information provision and for research that could not have been achieved through the use of only one perspective.